Supportive care needs and challenges experienced by women diagnosed with breast cancer in Kumasi, Ghana: A qualitative exploratory study - Abigail Owusu Sekyere; Merri Iddrisu; Hadiru Iddris Mumuni; Kennedy Dodam Konlan (PLoS ONE, 2025)
Introduction Globally, breast cancer (BC) remains the main cause of illness and death among women. A diagnosis with BC can be emotionally devastating and draining and these could predispose women diagnosed of BC to numerous psycho-emotional challenges. Aim We explored the supportive care needs and challenges experienced by women diagnosed with breast cancer in Kumasi, Ghana. Methods We used an exploratory descriptive design in which qualitative data via in-depth interviews was collected from fifteen women diagnosed with BC and receiving care at the Komfo Anokye Teaching Hospital in Kumasi, Ghana. A pre-tested, semi-structured interview guide was used for the data collection. The interviews were recorded using an audiotape and the audio files were transcribed verbatim. Thematic analysis was carried out with the aid of Nvivo 10.0. Results The analysis of the transcripts of interviews generated the following themes regarding supportive care needs: information needs, psychological needs and challenges experienced post BC diagnosis. On the information needs, we identified the following sub-themes; in adequate patient-specific information, challenges of disease disclosure and inadequate information on the availability of supportive care services. Regarding the psychological needs, the following sub-themes were identified: Loss of positive attitude to life, feelings of alienation and the need for moral support. On the main theme of challenges experienced by the women post BC diagnosis, the following sub-themes were identified; financial and geographical constraint in accessing care for BC, formal referral bureaucracy hindering access to care for BC and broken extended family system in Ghana. Conclusion Women diagnosed with BC in Ghana are psychologically and emotionally drained and they do not have adequate information on supportive care services available to help them cope after diagnosis. We recommend that psychological care and counselling be integrated into BC care using clinical psychologist or nursing staff with specialization in counselling and psychotherapy. We further recommend that regular information sessions are instituted at the various outpatient departments providing care for BC patients by nurse managers to provide women diagnosed with BC with information about supportive care services available.